Benjamin Dober, "Ethik des Trostes. Hans Blumenbergs Kritik des Unbegrifflichen" - Marras, Luca (Filosofia, 2020)
Review of Benjamin Dober’s book on Hans Blumenberg. This work can be read in first approximation as an introduction to Blumenberg’s philosophical anthropology within his historical context, but it also aims to find out in the anthropological premises of Blumenberg’s thought the key to investigate the ethical dimension of his works on nonconceptual forms such as the myth and the metaphor, a dimension which is not immediately evident in Blumenberg’s books.